Lessons Taught and Learned from the Operation of the Solar Energy E-Learning Laboratory - Eleftheriou, Polyvios C.; Michaelides, Ioannis M. (International Journal of Online and Biomedical Engineering (iJOE), 2009)
The solar energy e learning laboratory (solar e-lab) in Cyprus is a good example of a web-based, remote engineering laboratory. It comprises a pilot solar energy conversion plant which is equipped with all necessary instrumentation, data acquisition, and communication devices needed for remote access, control, data collection and processing. The impact that the solar e-lab had during its nearly 5 years of operation is indeed high. Throughout this period, the solar e-lab has been accessed by users from over 500 locations from 79 countries spread all over the world. In the period of November 2004 to October 2008, more than a million visits were recorded, out of which 25000 have registered on the site and surfed through studying the supplied material. Around 1000 hits concerned registered users that passed the pre-lab test and performed the experimentation part.The four years of operation of the solar e-lab demonstrated how the Internet can be used as a tool to make the laboratory facilities accessible to engineering students and technicians located outside the laboratory, including overseas. In this way, the solar energy e-learning lab, its equipment and experimental facilities were made available and shared by a number of interested people, thus widening educational experiences. Judging from the online evaluation reports that were received from the solar e-lab users during the last 2 years of operation, it can be concluded that there is nearly excellent satisfaction by the users.